Genus Protanilla Taylor, 1990 (HYMENOPTERA: FORMICIDAE: LEPTANILLINAE) from Sumatra, with the description of a new species - Rijal Satria,; Dwi Hilda Putri,; Yuni Ahda, (Penerbit Universiti Kebangsaan Malaysia, 2023)
We herein report the first record of the genus Protanilla Taylor,1990 from Sumatra, Indonesia. A new species of this genus is described and illustrated based on the worker caste under the name Protanilla eguchii sp. nov. This species was collected from the leaf-litter layer in a highland forest in West Sumatra Province. This species is discriminated well from the other named congeners by a combination of the following characteristics: body uniformly reddish yellow, with antenna and legs paler; relatively large in size; head in full-face view with posterior margin almost straight, and anterolateral corner not forming a distinct, tooth-like prominence; antennal scape long, slightly exceeding posterior margin of head; antennal segments 2–3 somewhat conical and longer than wide; antennal segments 4–11 nearly as long as wide; petiole in lateral view with its ventral outline of subpetiolar process sinuate. An update information is also given to the worker-based key to the species of the genus Protanilla.